Maladaptive behaviors in disasters: case study evaluation of Hurricane Hugo, Hurricane Katrina and the Haiti Earthquake - Milsten, Andrew M.; Kang, Christopher S.; Nemeth, Ira (Frontiers in Public Health, 2024)
Maladaptive behaviors during a disaster refer to actions that do not benefit the individual or society. Quarantelli highlights several maladaptive behaviors myths associated with disasters: widespread antisocial behavior, passivity, role conflict or abandonment, and sudden widespread mental health breakdowns (1). Despite early work reporting these myths, the common perception is that maladaptive behaviors such as rioting, looting, panic, and criminal conduct are prevalent in the wake of disasters. This is despite research by de Ville de Goyet and Arnold which has called on public officials and the media to stop propagating false disaster myths (2, 3). The classic academic response has been that this is a misconception and that, in fact, such behaviors are a very small part of the overall disaster and are mostly non-existent. Misconceptions about the prevalence of maladaptive behaviors can lead to inappropriate resource allocation, such as allocating extra police officers to prevent looting when the overall crime rate for the most part, decreases during disasters (4). Furthermore, while there are several persistent maladaptive behaviors myths, this is confounded by the presence of actual negative behaviors post disaster: false damage claims, insurance fraud, illegally obtaining relief supplies, failure to provide contracted repair services, hoarding of essential items, psychological trauma (which can lead to intergenerational transmission of the disaster memory) and medications and price gouging (5).When reading lay-press articles about recent disasters, it appears that these behaviors are on the rise. This raises the question: Has there been a change in the basic human reaction to disasters and are maladaptive behaviors on the rise? This review article focuses on case studies from three natural disasters: Hurricanes Hugo and Katrina, and the Haiti Earthquake. The goal of this review article is to evaluate these three natural disasters for evidence of maladaptive behaviors.